SOME ASPECTS OF REPRODUCTIVE POTENTIALS OF A CAPTIVELY MAINTAINED STOCK OF ALECTORIS CHUKAR: FECUNDITY, HATCHABILITY AND SURVIVAL RATE - N. Zahra; F. Abbas; S. Janjua; S. Jafar (Journal of Animal and Plant Sciences, 2015)
The current study was conducted to examine hatchability and fertility traits of Alectoris chukar. During the period of three months (March to May), total 348 eggs were obtained from 48-60 weeks old Alectoris chukar for this study. The external egg characters measured were egg color (EC), egg length (EL), egg breadth (EB), egg shape index (ESI), shell thickness (ST), membrane thickness (MT) and their relation to hatchability and fertility. Eggs were also categorized as infertile, hatched and unhatched eggs. Egg shell coloration and pigmentation also affects the fertility and hatchability of eggs. Light Creamy with Small Spots (LCSS) showed higher fertility and hatchability rate. EL, EB and ESI shows no significant effect on the fertility and hatchability. ST has showed a higher significant difference between the hatched, unhatched and infertile eggs while MT shown no significant difference between the infertile and hatched eggs. But MT varied significantly between hatched and unhatched eggs. Fertility and hatchability of Alectoris chukar are also affected by ST and MT. Temperature is an important physical factor that determines survival rates in Alectoris chukar. The egg production rate was higher in mid-March and two peaks in fatality were recorded in the month of April, June and July. Thus, the result of this study also indicates that when conditions are properly maintained, chukar partridges can be easily raised in captive conditions. these were significantly associated with hatchability
Keywords: Alectoris chukar; Hatchability; fertility; egg shells; membrane thickness; pigmentation.